Agile Governance in Urban Village Level Digital Public Service: A Study of the SIKECE Website for the Pangkalan Kerinci Timur - Denny Amansyah; Rury Febrina; Baskoro Wicaksono; Meris Essio Mento; Margina Ferlan (JOURNAL OF GOVERNMENT SCIENCE, 2026)
Digital transformation has driven significant changes in public service delivery, including at the urban village level. However, studies on the implementation of agile governance in website-based public services at the local level remain limited. This study aims to analyze the implementation of agile governance principles in digital public services through the SIKECE website in Pangkalan Kerinci Timur Urban Village. This research employs a descriptive qualitative approach, with data collected through interviews, observations, questionnaires, and documentation. Informants were purposively selected, comprising website managers and community members as service users. Data were analyzed qualitatively based on the six principles of agile governance. The findings reveal that the SIKECE website has successfully implemented agile governance principles, including good-enough governance, business-driven, human-focused, quick-win-oriented, a systematic and adaptive approach, and a simple design with continuous refinement. This implementation enhances efficiency, accuracy, responsiveness, and accessibility of public services, particularly in administrative processes such as certificate issuance. Nevertheless, several challenges remain, including gaps in digital literacy and limitations in technological infrastructure. This study contributes empirically to the literature on agile governance at the grassroots level and highlights the importance of strengthening technological capacity, stakeholder collaboration, and continuous development of digital systems to achieve inclusive and adaptive public service delivery.